2012
DOI: 10.5209/rev_sjop.2012.v15.n1.37295
|View full text |Cite
|
Sign up to set email alerts
|

Family Functioning and Socioaffective Competencies of Children in the Beginning of Schooling

Abstract: The aim of this short term longitudinal study, based on the system theory, was to test the association between different aspects of family functioning of preschoolers and their socioaffective competencies at the end of the first grade. The total sample included 278 children (137 boys and 141 girls) and their families. The analysis of variance results regarding the aspects of family cohesion and harmony showed that preschoolers from more cohesive families display more social skills, while those from more confli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…This dimension is essential for the development and consolidation of social responsibility as a civic-ethical and personal maturation component. The family is a space in which to enhance interpersonal relationships and to acquire the values of responsibility (Hammes et al, 2013;Mínguez, 2013). 4.…”
Section: Introductionmentioning
confidence: 99%
“…This dimension is essential for the development and consolidation of social responsibility as a civic-ethical and personal maturation component. The family is a space in which to enhance interpersonal relationships and to acquire the values of responsibility (Hammes et al, 2013;Mínguez, 2013). 4.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been observed that an inadequate emotional development often leads to irritable and impulsive children with little control, prone to externalizing behavioral problems in childhood or later in adolescence or adulthood, who can exhibit dysfunctional behavior and even break the law (Bandura, 1999; Eisenberg et al, 2000; Caprara et al, 2010; Justicia and Cantón, 2011; Mestre et al, 2012; Simone et al, 2012; McMahon et al, 2013; Llorca-Mestre et al, 2017a). …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a good deal of research has been conducted in the domain of early school adjustment, given that problems with school tend to persist throughout elementary school (Hausar-Cram, Durand, &Warfield, 2007; Hammes, Crepaldi, & Bigras, 2012; Ladd & Dinella, 2009). Ladd and colleagues have focused much of their work on the role of peer relationships in children’s academic functioning (Buhs, Ladd, & Herald, 2006; Ladd, 1999, 2006; Ladd & Burgess, 1999; Ladd, Herald-Brown, & Reiser, 2008).…”
mentioning
confidence: 99%